Production of hydrogen-rich syngas from methane reforming by steam microwave plasma - Choi, Dae Hyun; Chun, Se Min; Ma, Suk Hwal; Hong, Yong Cheol (Journal of industrial and engineering chemistry (Seoul, Korea), 2016)
•The steam microwave plasma contains highly active species and high-temperature plasma flame.•The steam plasma provides eliminating the need for catalysts in steam reforming reaction.•Methane reforming reaction by using steam plasma is showing high H2 concentration more than 70-vol.%. Steam-methane reforming (SMR) is most commonly carried out in a catalytic reactor at temperatures from 700 to 1000°C. During the reforming reaction, the catalyst agglomerates under the high temperatures, showing degradation of catalytic performance with carbon deposition on the catalyst surface. Here, we report methane reforming in a steam plasma generated by microwaves at atmospheric pressure without the use of catalysts. The plasma reforming system is mainly composed of a 2.45GHz microwave plasma torch and a plasma nozzle. Methane gas is introduced into the steam microwave plasma, which is stabilized by a swirl flow. The steam microwave plasma provides highly active species and a high-temperature plasma flame, enhancing the chemical reaction rate and eliminating the need for catalysts. We investigated the dependence of the hydrogen concentration on the steam to carbon ratio at a given plasma power. Using a specially designed plasma nozzle, we achieved high hydrogen concentrations (>70vol.%) in the effluent streams.